Práticas de laboratório : uma análise dos entendimento(s) e uso(s) apontados por professores de matemática em Aracaju-SE - Jarske, Érica de Oliveira (2014)
This study aimed to analyze understand(s) and use(s) that mathematics teachers make of laboratory practice in their classes. For this, practices of twenty-one teachers from the state network of Sergipe , in Aracaju, were investigated by means of questionnaires and interviews . For a discussion of the conceptions of Laboratory Mathematics (LEM) and laboratory practice lab, were taken as the main reference work Tahan (1962), Aguiar (1999), Benini (2006), Lorenzato (2006) and Rodrigues (2011), which describe the LEM not only as a specific physical space, but also as an approach taken by the teacher. Were considered in this investigation further searches of the Trindade (2012), Guimarães (2012) and Lima (2013), to establish an understanding of two possibilities for the use of laboratory practice in mathematics classrooms, as Resource or Methodology. In the first case, the goal is to fix concepts already studied, and the handling of the material by the student occurs after initial explanation of the subject by the teacher, and in the second case, as Methodology, the experimental activity is the starting point for the study of content, allowing the student to the construction of concepts. From the speech of teachers, it is clear that a minority of surveyed teachers often use laboratory practice in mathematics classrooms, and that the registered activities, is privileged to use manipulatives and games. On the way of use of the subject laboratory practice, it was found that there is a certain balance between Resource use and Methodology. From an analysis of the practices described by the subjects, it is clear that laboratory practices are still absent from the classes of most subjects in this study, although the teachers themselves recognize the value of experimental activity for student learning.